2022
DOI: 10.1007/s13346-022-01246-y
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic lipolysis rate for systematic design of lipid-based formulations

Abstract: Lipid-based formulations (LBFs) are used by the pharmaceutical industry in oral delivery systems for both poorly water-soluble drugs and biologics. Digestibility is key for the performance of LBFs and in vitro lipolysis is commonly used to compare the digestibility of LBFs. Results from in vitro lipolysis experiments depend highly on the experimental conditions and formulation characteristics, such as droplet size (which defines the surface area available for digestion) and interfacial structure. This study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Surfactants occur in saliva with a surface tension of 53-65mN/m, gastric fluid (43-54mN/m), the small intestine as bile salts (25-28mN/m which may also be present in gastric fluid) and in DWD (22-35 mN/m) [19][20][21][22][23]. An in vitro study to show how SF influence the digestibility of the fat tricaprylin, in the presence of the SF polysorbate 80 found that at low SF concentrations and in the presence of other types of SF (bile salts and phospholipids), adsorbed SF molecules can be displaced and allow lipolysis to occur in a concentration dependent manner [24]. Research involving the use of SF to prevent GERD was not found to be reported, possibly because lingual and gastric surfactants are not available for purchase and were not found included in standard (INFOGEST) in vitro gastric digestion methods [25].…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants occur in saliva with a surface tension of 53-65mN/m, gastric fluid (43-54mN/m), the small intestine as bile salts (25-28mN/m which may also be present in gastric fluid) and in DWD (22-35 mN/m) [19][20][21][22][23]. An in vitro study to show how SF influence the digestibility of the fat tricaprylin, in the presence of the SF polysorbate 80 found that at low SF concentrations and in the presence of other types of SF (bile salts and phospholipids), adsorbed SF molecules can be displaced and allow lipolysis to occur in a concentration dependent manner [24]. Research involving the use of SF to prevent GERD was not found to be reported, possibly because lingual and gastric surfactants are not available for purchase and were not found included in standard (INFOGEST) in vitro gastric digestion methods [25].…”
Section: Introductionmentioning
confidence: 99%